The Guerilla Chief, and Other Tales - Reid, Mayne, 1818-1883 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Guerilla Chief, and Other Tales" by Mayne Reid is a historical fiction work written in the late 19th century. The narrative revolves around events set during the Mexican-American War, showcasing the experiences and thoughts of soldiers in the aftermath of battle, including themes of valor, conflict, and personal sacrifice. The main character is a soldier who grapples with feelings of frustration at missed opportunities for glory and a sense of camaraderie towards his foes, revealing complex human emotions against a backdrop of war. At the start of the story, we are introduced to the setting of Cerro Gordo, where the protagonist reflects on the battle fought the previous day between American and Mexican armies. As the American troops celebrate their victory, the protagonist$1 (Bs attention is drawn to the Mexican leader Santa Anna, who narrowly escapes capture. His disappointment at being ordered to guard a battery instead of participating in the battle leads him to witness the chaotic retreat of Mexican soldiers. The narrative begins to unfold as he encounters a wounded soldier, Calros Vergara, and his sister, Lola, whose dangerous situation is exacerbated by the threat posed by a rogue captain named Ramon Rayas. The tension escalates as loyalties, affiliations, and the brutality of war intertwine with themes of love and protection, laying the groundwork for the unfolding tale. (This is an automatically generated summary.)s
The guerilla chief -- Despard, the sportsman -- A case of retaliation -- The broken bitt -- A turkey hunt in Texas -- Trapped in a tree -- The black jaguar: an adventure on the Amazon.
Release date is 2011-02-08
Produced by Nick Hodson of London, England
Keywords: Fiction